2002
DOI: 10.1002/cbm.484
|View full text |Cite
|
Sign up to set email alerts
|

What are adolescent antecedents to antisocial personality disorder?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
126
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 17 publications
11
126
3
2
Order By: Relevance
“…While other studies have failed to replicate this finding (Capaldi & Stoolmiller, 1999), adolescents with elevated depression and conduct problems seem to have particularly poor outcomes. For example, depression among clinic-referred adolescents with conduct disorder has been shown to be a particularly robust predictor of later antisocial personality disorder (Loeber et al, 2002). On the other hand, high levels of anxiety/withdrawal may actually buffer adolescents with significant conduct problems from experiencing long term negative outcomes.…”
Section: Internalizing Problems and Alcohol Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…While other studies have failed to replicate this finding (Capaldi & Stoolmiller, 1999), adolescents with elevated depression and conduct problems seem to have particularly poor outcomes. For example, depression among clinic-referred adolescents with conduct disorder has been shown to be a particularly robust predictor of later antisocial personality disorder (Loeber et al, 2002). On the other hand, high levels of anxiety/withdrawal may actually buffer adolescents with significant conduct problems from experiencing long term negative outcomes.…”
Section: Internalizing Problems and Alcohol Use Disordersmentioning
confidence: 99%
“…For example, Marmorstein and Iacono (2003) noted that adolescents with conduct disorder and elevated depressive symptoms may repeatedly use substances to manage their negative affective states because they are relatively unconcerned about violating social norms. Interestingly, longitudinal evidence also suggests that high levels of depression are associated with the progression from childhood conduct disorder to antisocial personality disorder in young adulthood (Loeber et al, 2002). As a result, young adolescents with co-occurring depression and conduct problem symptoms may be at particular risk for developing a severe form of alcoholism with antisocial features by young adulthood.…”
Section: Interactive Effects Of CD and Depressionmentioning
confidence: 99%
“…The APP index is a summary measure of the raw scores for 15 items, such as arguing a lot, being mean to others, lack of guilt, lying, threatening people, fighting, and having a bad temper. This DSM-oriented scale was included here to allow for a continual examination of developmentally appropriate problem behaviors across the age chunks, because ODP is one of the disruptive disorders that may be diagnosed during childhood and adolescence, and perspectives within developmental psychology have argued that it is part of a continuum as a diagnostic precursor to CD, and then APP later in life [see e.g., American Psychiatric Association, 2000; Loeber et al, 2002].…”
Section: Independent and Control Variablesmentioning
confidence: 99%
“…Among adolescents attending outpatient mental health clinics, Loeber et al (2002) found that the association between marijuana use and the development of APD was stronger than the association between CD and the development of APD.…”
mentioning
confidence: 91%
“…Substance abuse may increase risk for APD because it increases exposure to deviant peers, increases the need to obtain money for substance use, and can impair decision making Loeber et al, 2003). Among adolescents attending outpatient mental health clinics, Loeber et al (2002) found that the association between marijuana use and the development of APD was stronger than the association between CD and the development of APD.Internalizing disorders have also been proposed to influence the development of APD. Several studies suggest that depression increases risk for developing APD (Bardone, Moffitt, Caspi, & Dickson, 1996;Loeber et al, 2002;Sourander et al, 2005).…”
mentioning
confidence: 99%